2010
DOI: 10.1021/nn901821h
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Study of Naturally Occurring Defects in Self-Assembled Monolayer Formation

Abstract: One of the major challenges for nanofabrication, in particular microcontact printing (mu-CP), is the control of molecular diffusion, or "ink spreading", for the creation of nanopatterns with minimized "smudging" at pattern boundaries. In this study, fully atomistic computer simulations were used to measure the impact of naturally occurring domain boundaries on the diffusion of excess alkanethiol ink molecules on printed alkanethiol self-assembled monolayers (SAM). A periodic unit cell containing approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
50
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 50 publications
6
50
0
Order By: Relevance
“…The easy preparation of SAMs with different terminal chemical functionalities has made them convenient for far-reaching and numerous applications, including bio-related technologies such as biosensors and medical implants, nano-and microfabrication, nanodevices, and corrosion protection. Experimental microscopy studies have long shown that SAMs have high concentrations of defects [1][2][3]; in some cases, as with the nanofabrication method of microcontact printing, naturally occurring imperfections in the SAMs were shown to play a beneficial role in the process [4]. In most cases, however, defects in the monolayers can have unexpected and perhaps undesirable consequences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The easy preparation of SAMs with different terminal chemical functionalities has made them convenient for far-reaching and numerous applications, including bio-related technologies such as biosensors and medical implants, nano-and microfabrication, nanodevices, and corrosion protection. Experimental microscopy studies have long shown that SAMs have high concentrations of defects [1][2][3]; in some cases, as with the nanofabrication method of microcontact printing, naturally occurring imperfections in the SAMs were shown to play a beneficial role in the process [4]. In most cases, however, defects in the monolayers can have unexpected and perhaps undesirable consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Though molecular simulation can offer unique insights into the consequences of SAM structural imperfections, it has only rarely been done [5][6][7][8][9]; limitations of small simulation cell sizes and/or insufficient sampling times have prevented the explicit exploration of defects in typical SAM modeling studies [4]. We have employed the enhanced sampling method parallel tempering metadynamics using the well-tempered ensemble (PTMetaD-WTE), which we have used successfully in several prior studies to study peptide/protein adsorption at interfaces [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular modeling at the classical atomistic level has already proved to be useful in the interpretation of the behavior of a SAM [9,10]; in particular, it has been successfully applied to the study of elastic properties of azobenzene SAMs at the nanoscale [11].…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Strong covalent grafting produces robust assemblies, however irreversible binding to the semiconductor substrate may lead to substantial fluctuations in molecular packing density and formation of domains with variable average orientation. 1,13,14 In spite of the intrinsic topological disorder of organic monolayers (OML) covalently bound to semiconductor (SC) surfaces, electrical transport properties of such M-OML-SC devices have been widely studied due to their relatively low density of electrically active defects at the OML-Si interface, at least in their as-grown state. 28,32,34,[38][39][40][41][42] Linear saturated (n-alkyl) chains play the role of a nanometer-thick tunnel barrier (TB); however steric molecular constraints do not allow a full passivation of Si(111) surface sites, which remain subject to post-grafting oxidation at the ambient.…”
mentioning
confidence: 99%